ПОДОЛАННЯ ПРОБЛЕМИ ТРЕТЬОЇ ГАРМОНІКИ В ТЕОРІЇ АКТИВНОЇ ФІЛЬТРАЦІЇ ТРИФАЗНИХ ТРИПРОВІДНИХ СИСТЕМ ЕЛЕКТРОЖИВЛЕННЯ - Артеменко, М.Ю.; Кутафін, Ю.В.; Федорченко, П.; Чопик, В.В.; Шаповал, І.A. (Інститут електродинаміки Національної академії наук України, 2025)
In this paper, the mechanism of occurrence and a quantitative assessment of the third harmonic effect in the instantaneous active current vector of a three-phase power supply system with symmetrical sinusoidal source voltages in the presence of line load asymmetry are elucidated. It is shown that additional filtering of the instantaneous reactive power pulsating component of the consumed three-phase current eliminates the problem of the third harmonic and fully corresponds to shunt active filtering by the integral orthogonal components of the unbalance power. A new method of shunt active filtering by integral orthogonal components of unbalance power is proposed, which uses the active and reactive powers of individual phases of a three-phase three-wire power supply system. Computer simulations have confirmed the effectiveness of the active filtering method based on the measurement of active and reactive powers of individual phases.